Elementary School Teachers' Understanding of Inquiry Skills and Scientific Attitude - Rif'at Shafwatul Anam; Ucu Rahayu; Mestika Sekarwinahyu; Amalis Sapriati (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study aims to assess elementary school teachers' inquiry skills and scientific attitudes related to science. The instrument used in this study evaluates four groups of skills: conceptualizing and planning design, implementation, analysis, interpretation, and communication. Additionally, it assesses six categories of scientific attitudes: the nature of science, the basis of science, characteristics of scientists, goals of science, benefits of science, and responses regarding scientists. This research instrument underwent validation by two experts in the field of science. Validation results using Kendall's Tau calculations showed a value of 0.853 for the inquiry ability instrument and 0.807 for scientific attitude, and both falling into the â€˜very highâ€™ category. The study involved 49 elementary school teachers. Findings revealed that teachers' inquiry skills were categorized as 'weak', indicated by an average percentage below 50% in each skill group. Regarding scientific attitude, respondents' responses varied significantly between positive and negative statements, despite similarities found in two categories: 'basic science' and 'purpose of science'. This study highlights the necessity to consider the the learning process science, particularly emphasizing the development of inquiry skills and fostering positive scientific attitudes, from elementary school through university education.Keywords: inquiry skills, scientific attitudes, elementary teacher.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana keterampilan inkuiri guru baik dari sisi proses maupun sikap ilmiah terkait dengan sains. Proses yang diujikan dalam instrument ini terdiri dari empat kelompok keterampilan: mengkonsepsi dan merencanakan desain, implementasi, analisis dan interpretasi, serta mengkomunikasikan. Pada sikap ilmiah terdiri dari enam kategori yaitu: sifat dari ilmu sains, dasar ilmu sains, hal yang dimiliki ilmuan, tujuan ilmu sains, manfaat ilmu sains, dan tanggapan mengenai ilmuan sains. Instrumen penelitian ini telah dilakukan validasi pada dua orang doktor pada bidang sains. Berdasarkan hasil validasi menggunakan perhitungan Kendallâ€™s Tau memiliki nilai sebesar 0,853 untuk instrument kemampuan inquiry dan nilai sebesar 0,807 untuk sikap ilmiah serta keduanya termasuk ke dalam kategori sangat tinggi. Responden dalam peneitian ini terdiri dari 49 orang guru sekolah dasar yang didapatkan bahwa keterampilan inkuiri berada pada kategori â€œlemahâ€ hal ini ditunjukkan dengan persentase rata-rata responden pada setiap kelompok dibawah 50%. Sedangkan pada sikap ilmiah didapatkan bahwa respon responded terhadap pernyataan sikap ilmiah antara pernyataan positif dan negatif cukup berbeda walaupun ada dua kategori sikap ilmiah yang sama responnya. Dua kategori itu adalah pada â€œdasar ilmu sainsâ€ dan â€œtujuan dari sainsâ€. Studi ini menunjukkan bahwa proses pembelajaran sains dari SD sampai dengan perguruan tinggi perlu untuk diperhatikan terutama hal yang berkaitan dengan keterampilan inkuiri dan sikap ilmiah.Kata kunci: kemampuan inkuiri, sikap ilmiah, guru sekolah dasar